Implementation and evaluation of efficiency of gas preliminary drying system during operation of process equipment of complex gas treatment unit - O. Yu. Manikhin; V. V. Shalay (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
In order to increase the efficiency of the absorption dehydration of the integrated gas treatment unit during peak summer operating modes, when the temperature of the dried gas significantly exceeds +25°C, a preliminary dehydration system has been introduced into the processing flow chart. The implemented technical and technological improvements both of the internal elements of the separation equipment and the piping system of the gas dehydration shop made it possible to reduce the carryover of droplet moisture from the separation and absorption equipment, as well as to ensure compliance with the current standards for commercial gas for the key parameter dew point temperature, in compliance with the required technological reserve